2013
DOI: 10.17265/2159-5542/2013.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Tease: Exploring Men’s Constructions of Paying for Sex in South Africa

Abstract: Sex work in South Africa is poorly understood. Sex work and paying for sex are still considered illegal in South Africa. Research focus thus far has been on sex workers and their experiences. There exists a paucity of research literature on the perceptions of the client. This research focused on how South African men construct paying for sex.Semi-structured interviews were conducted to explore male clients' experiences of paying for sex. Through thematic analysis various themes emerged. Three main themes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Nonetheless, several studies have shown that men who purchase sex relate to and navigate in relation to perceptions of deviance and normality, for example by distinguishing between various types of paid sex and various contexts where such sex may occur based on their perceived morality and normativity. Furthermore, men who purchase sex seem to make a distinction between deviant aspects and forms of commercial sex, and their own experience and practice (Lahav-Raz et al, 2023;Prior & Peled, 2021;Wepener et al, 2013). Previous studies have shown differences in experiences and attitudes among men who purchase sex based on whether they had purchased sex frequently or only once (Shilo et al, 2021).…”
Section: Understanding Individual Experiences Of Purchasing Sexmentioning
confidence: 99%
“…Nonetheless, several studies have shown that men who purchase sex relate to and navigate in relation to perceptions of deviance and normality, for example by distinguishing between various types of paid sex and various contexts where such sex may occur based on their perceived morality and normativity. Furthermore, men who purchase sex seem to make a distinction between deviant aspects and forms of commercial sex, and their own experience and practice (Lahav-Raz et al, 2023;Prior & Peled, 2021;Wepener et al, 2013). Previous studies have shown differences in experiences and attitudes among men who purchase sex based on whether they had purchased sex frequently or only once (Shilo et al, 2021).…”
Section: Understanding Individual Experiences Of Purchasing Sexmentioning
confidence: 99%